Flora and Vegetation of Malkangiri District, Orissa, India - an Assessment - Sahu, D. K.; Biswas, S.; Dhal, N. K.; Brahmam, M. (Indian Forester, 2010)
Extensive and intensive field surveys have been conducted in different forest pockets of Malkangiri with a view to assess the floristic wealth of the district. A sum total of 381 species belonging to 275 genera and 92 Families were collected, identified and incorporated. Out of these, 373 species represent Angiospermae (304 species of Dicot and 69 species of Monocot families), 7 species of Pteridophytes (7 species of Ferns belonging to 7 genera) and 1 species of Gymnosperms. The ratio of monocot to dicot families, genera and species are 1:4.25, 1:4.13 and 1:4.40 respectively. Present exploration enumerates 235 herbs, 51 shrubs, 69 trees and 26 climbers. Out of total 84 families of angiosperms, the dominant families in ascending order are Fabaceae, Poaceae, Acanthaceae, Asteraceae, Euphorbiaceae, Malvaceae, Caesalpiniaceae, Rubiaceae, Lamiaceae, Combretaceae, Cyperaceae, Mimosaceae, Amaranthaceae and Scrophulariaceae. Study highlights the rich floristic diversity of the district.